2021
DOI: 10.3390/cells10092382
|View full text |Cite
|
Sign up to set email alerts
|

The Oncogenic Signaling Disruptor, NDRG1: Molecular and Cellular Mechanisms of Activity

Abstract: NDRG1 is an oncogenic signaling disruptor that plays a key role in multiple cancers, including aggressive pancreatic tumors. Recent studies have indicated a role for NDRG1 in the inhibition of multiple tyrosine kinases, including EGFR, c-Met, HER2 and HER3, etc. The mechanism of activity of NDRG1 remains unclear, but to impart some of its functions, NDRG1 binds directly to key effector molecules that play roles in tumor suppression, e.g., MIG6. More recent studies indicate that NDRG1s-inducing drugs, such as n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 126 publications
(438 reference statements)
1
22
0
Order By: Relevance
“…Metastasis suppression via up-regulation of the iron-regulated metastasis suppressor, NDRG1, is an important property of ligands designed as antitumor agents, ,, as metastasis is the major killer in cancer . The expression of NDRG1 in both cell-types was increased to varying extents by the thiosemicarbazones, with DpC and PPP4NpT demonstrating the greatest activity, while no up-regulation was observed with Bp2mT and PPP4ClpT (Figure A,B).…”
Section: Resultsmentioning
confidence: 97%
“…Metastasis suppression via up-regulation of the iron-regulated metastasis suppressor, NDRG1, is an important property of ligands designed as antitumor agents, ,, as metastasis is the major killer in cancer . The expression of NDRG1 in both cell-types was increased to varying extents by the thiosemicarbazones, with DpC and PPP4NpT demonstrating the greatest activity, while no up-regulation was observed with Bp2mT and PPP4ClpT (Figure A,B).…”
Section: Resultsmentioning
confidence: 97%
“…For example, in DNA damage contexts, NDRG1 was shown to translocate to the nucleus in bladder carcinoma cells [ 17 ], while hypoxic conditions in trophoblasts enhanced NDRG1 expression in the nucleus and cytoplasm [ 13 ]. The translocation of NDRG1 under hypoxic and DNA damaging conditions supports its function as a stress responsive gene [ 18 ]. Additionally, both phosphorylation and proteolytic cleavage of NDRG1, shown in HCC, prostate, colon, and pancreatic cancer cells have been associated with different localization implications [ 1 ].…”
Section: Ndrg1 Expression and Localizationmentioning
confidence: 99%
“…Sulforaphane (SFN) induces cell differentiation, melanogenesis and also inhibit the proliferation of melanoma cells [49].The transcription factor B cell lymphoma 6 (Bcl6) is essential in maintaining the lineage stability of Treg cells in TME [50]. N-myc downstream regulated gene 1 (NDRG1) has been identi ed as a protein involved in the differentiation of epithelial cells, which is an oncogenic signaling disruptor that plays a key role in multiple cancers [51]. Taken together, studies as mentioned above revealed the reasonability and accuracy of our SRS in SKCM tumorigenesis and development.…”
Section: Discussionmentioning
confidence: 99%